Preactivity during rotational jump landing - Bai, B.; Fukumoto, T. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to identify the the timing of the muscle preactivities of the hamstrings and quadriceps during landing from 180 and 360 degrees rotational jump. The subjects (n=10) participated in this study. The tasks were 180 and 360 degrees rotational jump. The electromyography (EMG) data was collected from the left leg muscles of all the individuals: the vastus medialis (VM), the rectus femoris (RF), the vastus lateralis (VL), the semimembranosus (SM) and biceps femoris (BF). In VL, 360 degrees was significantly faster than 180 degrees (p < 0.01). In the case of 180 degrees landing, the timing of preactivity of the hamstrings resulted in significantly earlier than the quadriceps (p < 0.01). As for 360 degrees landing, the timing of preactivity of SM resulted in significantly earlier than VM (P < 0.05). These results proved that rotational jump was necessary as a part of prevention programs.